PERMASALAHAN YANG DIHADAPI DALAM PELAKSANAAN SEKOLAH INKLUSI DI INDONESIA - Laura Tyas Pratiwi; Meilani Nur Maghfiroh; Dimas Septa Andika; Intan Nur Marcela; Awayna Faza Afifah (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2022)
Abstract: Children with special needs have the same rights as children in general to get an education. Unfortunately, the availability of adequate education for children with special needs is not adequate and equal. Because the provision of special schools only in big cities. Inclusive education comes as an alternative solution to overcome the social problems of Children with Special Needs (ABK). The purpose of establishing inclusive education is to minimize the impact caused by an exclusive attitude. In addition, inclusive education also has several problems because both schools, communities and teachers do not fully understand and know how to implement inclusive schools in accordance with existing rules. In this article using descriptive research methods to find out more deeply what problems are faced by schools, especially related to the implementation of inclusive education. society, and government.